2019
DOI: 10.1515/jpm-2018-0231
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of isolated clubfoot in twin compared to singleton gestations

Abstract: Background Our objective was to determine the predictive value of the prenatal diagnosis of isolated clubfoot in twin gestations compared to singleton gestations. Methods A prospectively entered ultrasound database was reviewed for all pregnancies scanned at our institution from 2002 to 2014. Cases of suspected clubfoot were identified. Neonates with associated anomalies or aneuploidy, and patients who delivered at other institutions were excluded. Neonatal charts were reviewed for the confirmation of clubfoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The 23 selected studies included a total of 2318 patients who were prenatally diagnosed with clubfoot by US and/or MRI, some included karyotyping through amniocentesis and/or CVS. 11 of the studies included information about whether or not the diagnosis was confirmed after birth (accuracy) [ 1 , 10 , 11 , 12 , 13 , 14 , 16 , 22 , 23 , 25 , 27 ], the rest of the studies were used to obtain information about the main methodology used for prenatal diagnosis of clubfoot, but did not provide any detail about its accuracy; therefore, this item was not assessed. The minimum age was the first trimester of pregnancy (the week was not specified) [ 8 , 18 , 23 , 25 , 26 ] while the maximum reported age was 28 weeks of pregnancy [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 23 selected studies included a total of 2318 patients who were prenatally diagnosed with clubfoot by US and/or MRI, some included karyotyping through amniocentesis and/or CVS. 11 of the studies included information about whether or not the diagnosis was confirmed after birth (accuracy) [ 1 , 10 , 11 , 12 , 13 , 14 , 16 , 22 , 23 , 25 , 27 ], the rest of the studies were used to obtain information about the main methodology used for prenatal diagnosis of clubfoot, but did not provide any detail about its accuracy; therefore, this item was not assessed. The minimum age was the first trimester of pregnancy (the week was not specified) [ 8 , 18 , 23 , 25 , 26 ] while the maximum reported age was 28 weeks of pregnancy [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The final studies selected by the reviewers included the following levels of evidence: 19 level III retrospective studies [ 1 , 2 , 7 , 9 , 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 21 , 22 , 25 , 26 , 27 ], 3 level II prospective comparative studies [ 8 , 11 , 20 ], 1 descriptive study of level III [ 19 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations